An Endocrine Jaw Lesion: Dentist Perspective in Diagnosis - Lavanya Kalapala; Surapaneni Keerthi sai; Suresh Babburi; Aparna Venigalla; Soujanya Pinisetti; Ajay Benarji Kotti; Kiranmai Ganipineni (Hindawi Limited, 2016)
Brown tumor is a rare nonneoplastic focal giant cell lesion that occurs in hyperparathyroidism patients with a prevalence rate of 0.1% in jaws. We report an extremely rare case of brown tumor in mandible of a 40-year-old female patient that presented as the first clinical manifestation of hyperparathyroidism. Dentist played a pivotal role in the present case by the early diagnosis of lesion and its intervention.